On dynamical systems and phase transitions for Q + 1-state P-adic Potts model on the Cayley tree - Mukhamedov, Farrukh (2010)
In the present paper we are going to investigate phase transition phenomena from the dynamical system point of view. Using the derived recursive relations we define one dimensional fractional p-adic dynamical system. We establish that if q is divisible by p, then such a dynamical system has two repelling and one attractive fixed points, in this case there exists the strong phase transition. If q is not divisible by p, then the fixed points are neutral, which implies the existence of the quasi phase transition.